(untitled) (Research, Society and Development, 2024)
The article analyzes female participation in leadership and innovation positions, highlighting the challenges and achievements in the pursuit of gender equality. This study aims to explore the intersections between female leadership and innovation, proposing recommendations for implementing strategies that promote a more inclusive and equitable environment. The methodology involves a bibliographic review of relevant studies on female leadership and innovation, based on theories such as female empowerment and diversity. Despite the advances, women still face barriers such as stereotypes and lack of representation, limiting their access to prominent positions. The text emphasizes the importance of female empowerment in teams, showing that the inclusion of women in positions of power promotes social justice, but is also an effective strategy for organizational success. The presence of women in leadership positions is associated with more inclusive decisions and a collaborative environment, increasing creativity. The article concludes that promoting female leadership is fundamental for a more equitable and sustainable future, emphasizing that diversity is key to progress in the global market. The research highlights the need for policies that support work-life balance and promote support networks to overcome the obstacles faced by women. In short, women’s inclusion in leadership and innovation is essential for sustainable development.